Quarantined Justice, Compromised Diversity: Barriers to Disability Inclusion in China’s Public Sector Employment - Qian Xue; Bo Chen (Social Inclusion)
Under the advocacy for diversity and inclusion within Chinese society, the judiciary has become a significant institution for the protection of marginalized groups, especially disabled people. Through proactive power expansion, the Supreme People’s Court has played a crucial role in scrutinizing employment discrimination in the private sector. However, the judiciary has paid less attention to the fact that government agencies failed to consider the value of workplace diversity and maintained ableist standards that preclude many disabled candidates from public sector positions. Due to the intrinsic political embeddedness within Chinese judicial systems, courts tended to adopt a strategy known as “quarantined enforcement” when confronted with discriminatory recruitment clauses issued by government‐tied entities. Social and political factors collaboratively shaped the intersectional marginalization of the disabled community in China. This article attempts to move beyond traditional legislative‐centric approaches and emphasize the judiciary’s role in minimizing the marginalization of disabled people. It argues that eliminating political barriers within the judiciary is crucial for achieving workplace diversity and employment equality.